Î“-(ï¬,Î´)-Derivation on Semi-Group Ideals in Prime Î“-Near-Ring: -(ï¬,Î´)-derivations on Semi-group Ideals in Prime - - Ahmed, Hiba A.; Majeed, Abdulrahman H. (Iraqi Journal of Science, 2020)
The main purpose of this paper is to investigate some results. When h is ï‡ -(ï¬ ,Î´) â€“ Derivation on prime Î“-near-ring G and K is a nonzero semi-group ideal of G, then G is commutative .